Saturday, May 8, 2010

how to prove it - ch3, sec3.3(Proofs Involving Quantifiers) ex

To prove a goal of the form xP(x):
Let x be arbitrary
[Prove P(x)]
Since x was arbitrary, we can conclude that xP(x)

Here it is very important to make no assumption about x. Main advantage of this strategy is that it enables you to prove a goal about all objects by reasoning about only one object. If you find yourself using a lot of "all x's" or "every x", then you are probably making your proof unnecessarily complicated by not using this strategy.


To prove a goal of the form xP(x):
Find a particular value x such that P(x) is true. Thus, xP(x)

Finding the right value to use for x may be difficult in some cases. One method that is sometimes helpful is to assume that P(x) is true and then see if you can figure out what x must be, based on this assumption.

Next important thing is to learn, how to use a given quantified sentence.


To use a given of the form xP(x):
We can use this by introducing a new variable x0 into the proof to stand for an object for which P(x0) is true. That is, you can now assume P(x0) is true.

To use a given of the form xP(x):
This is useful only when you're talking about some value a in your proof, you can always assume that P(a) is true.

In general, its a good strategy to simplify the goal as much possible by using the strategies we're learning.


======================================================================================

Ex-1 Given that x(P(x)Q(x)), so we can find a x0 s.t. P(x0)Q(x0). Suppose xP(x), it follows that P(x0) is true and hence Q(x0) is also true. Thus xQ(x) is true. So, xP(x)xQ(x) is true.


Ex-2 Scratch Work:

given:
goal: AB\C=ABC

Assume the hypotheses

given: AB\C=
goal: ABC x(xABxC)

Let x be arbitrary

given: AB\C=
goal: xABxC

Assume the hypotheses

given: AB\C= , xAB
goal: xC

we can not analyse goal any further, so let us analyze the givens now.

It is given that
AB\C=
¬xx(AB\C)
x¬(x(AB\C))
x¬(xAxBxC)
x[¬(xAxB)xC]
x(xABxC)

Hence xC


Formal Proof:
Let x be an arbitrary element of AB. Suppose A and B\C are disjoint, so it can not happen that x belongs to A and B but not C. So x must be an element of C. Thus xABxC. Since x is arbitrary, hence x(xABxC) or ABC. So, If A and B\C are disjoint then ABC


Ex-3
given:
goal: If AB\C then A and C are disjoint

Assume the hypotheses

given: AB\C
goal:
A and C are disjoint
= ¬x(xAxC)
= x(xAxC)
= x(xAxC)


Let x be arbitrary

given: AB\C
goal: xAxC

Assume the hypotheses

given: AB\C , xA
goal: xC

Formal Proof:
Let x be an arbitrary element of A and AB\C. It follows that x must belong to B\C, so x must not be in C. Hence, If AB\C and xA then xC. Since x is arbitrary, so If AB\C then A and C are disjoint.


Ex-4
Note: In this exercise P(A) means Power Set of A.

given: AP(A)
goal: P(A)P(P(A)) = x(xP(A)xP(P(A)))

Let x be arbitrary

given: AP(A)
goal: xP(A)xP(P(A))

Assume the hypotheses

given: AP(A), xP(A)
goal: xP(P(A)) = xP(A) = y(yxyP(A))

Let y be arbitrary

given: AP(A), xP(A)
goal: yxyP(A)

Assume the hypotheses

given: AP(A), xP(A), yx
goal: yP(A)

Since xP(A)
=> xA
and Since AP(A)
=> xP(A)
and Since yx, so yP(A)


Formal Proof:
Let x be an arbitrary element of P(A), it follows that xA. Since AP(A), so xP(A) and hence xP(P(A)). It means if AP(A) and xP(A) then xP(P(A)). Since x is arbitrary, it follows, if AP(A) then P(A)P(P(A))


Ex-5
(a) Yes, the empty set
(b) {}


Ex-6(a)
given:
goal: if x1 then y(y+1y-2=x)

Assume the hypotheses

given: x1
goal: y(y+1y-2=x)

in order to prove it, we have to find a y0 s.t. y0+1y0-2=x
=> y0+1 = x(y0-2)
=> y0+1 = xy0-2x
=> xy0-y0 = 1+2x
=> y0 = 1+2xx-1

It is defined since (x-1)0.

Formal Proof:
Assume y = y0 = 1+2xx-1
Now, y+1y-2
= y0+1y0-2
= (1+2xx-1)+1(1+2xx-1)-2
= 1+2x+x-11+2x-2x+2
= 3x3
= x

Thus, If x1 then there exists a real number y s.t. y+1y-2=x

Ex-6(b)
For y+1y-2=x to be true
y = 1+2xx-1
which is defined only when (x-1)0 => x1

Thus, if there exists a real number y s.t. y+1y-2=x then x1


Ex-7 Let x be an arbitrary real number and x > 2.
For a real number y = x+x2-42
x2-4 is defined because x>2 => x2>4 => x2-4>0

Now, y+1y
= x+x2-42 + 2x+x2-4
= (x+x2-4)(x+x2-4)+42(x+x2-4)
= x2+(x2-4)+2xx2-4+42(x+x2-4)
= 2x2+2xx2-42(x+x2-4)
= x

Thus, for any real number x, if x > 2, then there exists a real number y s.t. y+1y = x.


Ex-8
Note: F in this ex means a Family of Sets.

given:
goal: if AF then AF

Assume the hypotheses

given: AF
goal: AF x(xAxF)

Let x be arbitrary

given: AF
goal: xAxF

Assume the hypotheses

given: AF, xA
goal: xF yF(xy)

Since, xA and AF, so y = A satisfies the goal.

Formal Proof:
Suppose AF and x be an arbitrary element of A. Since F is union of all the sets in F and that includes A, it follows that xF. Thus if AF then xAxF. Since x is arbitrary, hence If AF then AF


Ex-9 Suppose AF and x be an arbitrary element of F. Since F is intersection of all sets in F, it follows that xA. In other words, If AF and xF then xA. Since x is arbitrary, we can conclude that If AF then FA


Ex-10
given: F is a non-empty family of sets, B is a set, AF(BA)
goal: BF

Formal Proof:
Let x be an arbitrary element of B. Since AF(BA), that is B is subset of each element of F, it follows that x must be an element of every set in F. So xF. Hence xBxF. Since x is arbitrary, Therefore BF


Ex-11
given:
goal: If F then F=

Assume the hypotheses

given: F
goal:
F=
¬x(xF)
x¬(xF)

Let x be arbitrary

given: F
goal:
¬(xF)
¬y(yFxy)
y(yFxy)

y= satisfies the goal, because no matter what x is, it can not be an element of

Formal Proof:
Suppose F. Now We will prove by contradiction that F=. Let x be an arbitrary element of F, it follows that x must belong to every element of F. Since F, so x should also belong to which is not possible, hence x can not belong to F. Since x is arbitrary, we can conclude that If F then F=


Ex-12
Note: F and G are families of sets.

given:
goal: If FG then FG

Suppose the hypotheses

given: FG
goal: FG

Formal Proof:
Suppose FG and Let x be an arbitrary element of F. By definition of F it follows that there must be atleast one element A of F s.t. xA. Since FG, so A should be an element of G also. That is we have xA and AG, so xG. Since x is arbitrary, Therefore If FG then FG


Ex-13 Suppose FG and x be an arbitrary element of G. By definition of G it follows that x must be an element of every element of G. Since FG, therefore x must be an element of every element of F also. So xF. Thus If FG then xGxF. Since x is arbitrary, we can conclude that If FG then GF


Ex-14
given:
goal:
iIP(Ai)P(iIAi)
x(xiIP(Ai)xP(iIAi))

Let x be arbitrary

given:
goal: xiIP(Ai)xP(iIAi)

Assume the hypotheses

given: xiIP(Ai)
goal: xP(iIAi)
xiIAi

Formal Proof:
Let x be an arbitrary element of iIP(Ai). It follows, there should exist atleast one kI s.t. xP(Ak).
So xAk
=> xiIAi
=> xP(iIAi)

Thus, if xiIP(Ai) then xP(iIAi). Since x is arbitrary, we can conclude that iIP(Ai)P(iIAi)


Ex-15
given: I
goal: iIAiiIP(Ai)

Let us try to see what it means for an arbitrary x to be an element of iIP(Ai)
xiIP(Ai)
=> iI(xP(Ai))
=> iI(xAi)

Formal Proof:
By definition of iIAi it follows that
iI(iIAiAi)
=> iI(iIAiP(Ai))
=> iIAiiIP(Ai)


Ex-16
given:
goal: If FP(B) then FB

assume the hypotheses

given: FP(B)
goal: FB

Formal Proof:
Suppose FP(B) and Let x be an arbitrary element of F. By definition of F it follows that there exists atleast one AF s.t. xA. Since FP(B), therefore AP(B) is also true. It follows that AB and hence xB. Thus, If xF then xB. Since x is arbitrary, we conclude that If FP(B) then FB


Ex-17
given: F and G are non-empty family of sets, every element of F is subset of every element of G
goal: FG

Formal Proof:
Let x be an arbitrary element of F. By definition of F it follows that there exists atleast on AF s.t. xA. Since every element of F is subset of every element of G, therefore A is subset of every element of G and hence AG. So xG. Since x is arbitrary, we conclude that FG


Ex-18(a) Suppose a|b and a|c, so there exists atleast two integers k1 and k2 s.t.
ak1=b ..... (i)
and
ak2=c ..... (ii)

adding eq (i) and (ii) we get
a(k1+k2)=(b+c)
since k1+k2 is another integer, so a|(b+c).

Ex-18(b) Suppose ac|bc and c0. There exists an integer k s.t. ack = bc
=> ack - bc = 0
=> c(ak - b) = 0
Since c0, therefore (ak - b) = 0
=> ak = b
=> a|b

Ex-19
(a)Let x and y be arbitrary real numbers and z = y-x2.
x + z
= x + y-x2
= 2x + y - x
= y + x

and
y - z
= y - y-x2
= 2y - y + x
= y + x

so x+z = y-z
Thus, for all real numbers x and y there exists a real number z such that x+z = y-z

(b) No, it wouldn't be justified as z = y-x2 might not be an integer even though x and y are.


Ex-20 The flaw is in the conclusion that "for every real number x, x2 < 0" because assumption of negation of the statement given in the theorem being true means just that "there exists atleast one real number x s.t. x2 < 0.


Ex-21
(a) x being an arbitrary element of A does not mean its an arbitrary element of B also.

(b) A = {1}; B{0,1}


Ex-22 Given proof does not consider y to be arbitrary. For a particular value of x = yy2+1, there is only one(not all real number) real number y s.t. xy2=y-x


Ex-23
(a) Let us focus on the second half of the proof given, which basically says A(FG) contradicts FG= because no such A can exist, which is not true.
Suppose A=, then clearly both, A(FG) and FG=, are true.

(b) A counter example is
F = {,{1}}
G = {,{3}}


Ex-24
(a) x and y are not considered completely arbitrary but equal.

(b) Theorem is incorrect. x = 2, y = 1 is a counterexample as x2+xy-2y2
= 4 + 2 - 2
= 4, which is non-zero


Ex-25 Let x be an arbitrary real number and y = 2. Let z be an arbitrary real number.
(x+z)2-(x2+z2)
= x2+z2+2z-x2+z2
= 2z
= yz
Thus, for every real number x there is a real number y s.t. for every real number z, yz = (x+z)2-(x2+z2)


Ex-26
(a) For goals of the form xP(x) we can immediately initiate the proof by assuming x arbitrary and P(x) true. And for given of the form $xP(x) also we can immediately initiate the proof by assuming one x0 that satisfies P(x0)
For both, the goal of the form xP(x) and given of the form xP(x), we can not immediately start the proof unless we find a value x0 of interest.

(b) Because negation of universal quantifier is existential quantifier and viceversa.

4 comments:

  1. Ex-23
    (a) The statement A ∈ F → A ⊆ ∪F is all right. I think the problem here is the last two statements. Since (∪F ∩ ∪G) = ∅ and A ⊆ (∪F ∩ ∪G), it follows that A = ∅, which is not a contradiction.

    ReplyDelete
  2. @Stavros : I agree, You're right in Ex-5(b) and Ex-23(a). Updating both in original post.

    ReplyDelete